PRACTICAL STUDY OF GPS ACCURACY DATA IZMERENIY METODOM BYSTROY STATIKI, S. POSTOBRABOTKOI V AUSPOS - ONLINE GPS PROCESSING SERVICE - Kamaliyev M.M., Камалиев М.М. (Рroblems of engineering and professional education, 2023)
This article provides quick statistics compiled by AUSPOS on the website www.ga.gov.au In this mode, an accuracy study of these GPS measurements is provided. Online GPS Processing Service These coordinates are now compared with the current coordinates.